2017
DOI: 10.1016/j.jacep.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Validation of the Lesion Size Index to Predict Lesion Width and Depth After Irrigated Radiofrequency Ablation in a Porcine Model

Abstract: In this in vitro model, FTI and LSI predicted RF lesion dimensions, whereas power and CF did not. The LSI predictive value was higher than that of FTI. Steam pops occurred only using high ablation power levels, regardless of the targeted LSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
135
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(141 citation statements)
references
References 12 publications
3
135
1
2
Order By: Relevance
“…In an in vitro model, the predictive value of LSI for lesion size was reported to be higher than that of FTI; however, the superiority of LSI for predicting the residual gap or DC was not validated in our human study. This discrepancy may possibly be explained by several factors.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…In an in vitro model, the predictive value of LSI for lesion size was reported to be higher than that of FTI; however, the superiority of LSI for predicting the residual gap or DC was not validated in our human study. This discrepancy may possibly be explained by several factors.…”
Section: Discussioncontrasting
confidence: 66%
“…The LSI is a novel index that can help predict the size of the lesion created by RF application. LSI is derived from a mathematical expression that incorporates CF, impedance, power, and duration of RF application . LSI represents an improvement over FTI in several respects .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FTI is a lesion metric that is included in multiple electroanatomic mapping platforms, while ablation index (AI) (Biosense Webster) is a proprietary algorithm combining CF, RF application duration, and power. AI calculation was derived in previous studies and is based on a complex formula incorporating RF power, RF duration, and CF, and lesion metric indices have been shown to correlate with lesion dimensions . Previous in vivo studies have suggested targeting AI values from 400 to 500 to create durable lesions in pulmonary vein isolation (PVI) procedures.…”
Section: Introductionsupporting
confidence: 55%